Importância da ecocardiografia transesofágica multiplanar no diagnóstico de tromboembolismo pulmonar - Galrinho, A (1999)
Pulmonary thromboembolism (PTE) is a clinical entity difficult to diagnose, its setting is often confused with other pathological entities. The inexistence of isotopic techniques in most centres and the difficulty and delay in performing a pulmonary angiography leads transesophageal echocardiography (TEE) to be, a method of increasing importance for its diagnosis. From January 1996 to November 1997, echocardiographic evaluation was requested for 33 patients due to clinical suspicion of pulmonary thromboembolism. A transthoracic assessment was made previously in 21 patients (average ages 58.3 years, 52% males) which had signs of right overload (dilatation of the right cavities, anomalous movement of the intraventricular septum and pulmonary hypertension) a TEE was performed. The TEE was negative in 10 patients (TEEn) without evidence of thrombi in the trunk and main branches of the pulmonary artery (PA); there was one death on this group for repeated pulmonary microembolisms confirmed by necropsy. The TEE was positive in 11 patients (TEEp) with evidence of thrombi in the PA trunk in 3 patients, bilaterally in both branches in 3 patients and in the right branch in 5 patients. There were dilatations of the right cavities in all patients, paradoxal movement of the interventricular septum and bulging of the intra-auricular septum to the left atria. Foramen ovale was detected in 2 patients. The best visualisation of the PA was achieved in the intermediate planes between 30-70 degrees and between 90-130 degrees (plane for transverse slice of the right branch of the pulmonary artery). In 7 patients with TEEp, PTE was confirmed by CT-scan (visualisation of the thrombi in the trunk and main branches of the PA) and/or ventilation-perfusion scintigraphy and/or pulmonary angiography. In three cases of massive pulmonary embolism in young patients, with severe pulmonary hypertension, thrombolysis was performed with rTPA, under TEE control before and after rTPA in one of the cases. In conclusion, transesophageal echocardiography is an easy technique to be performed in the case of clinical suspicion of PTE. The existence of a negative examination does not invalidate the existence of PTE since only the trunk and the main branches of the PA are accessible by this technique. The detection of thrombi at this level in patients with clinical suspicion of massive pulmonary embolism confirms the diagnosis and supports the indication of thrombolysis.